Odpowiedzi

2010-03-25T15:20:52+01:00
A)3a-3 = 3(a-1)
4+4x=4(1+x)
6m-6a=6(m-a)
b)8a-16 = 8(a-2)
15b+10 = 5 (3b+2)
16b-12c =4(4b-3c)
c)12x+36y = 12(x+3y)
y-3y= y(1-3)
15a²+12b= 3(5a²+4b)
d)24x²- 16y = 8(3x²-2y)
12a²-8b= 4(3a²+2)
10n-15m= 5(2n+3m)

3 2 3
Najlepsza Odpowiedź!
2010-03-25T15:21:06+01:00
A)
3a-3 = 3(a-1)
4+4x = 4(1+x)
6m-6a = 6(m-a)

b)
8a-16 = 8(a-2)
15b+10 = 5(b+2)
16b-12c = 4(4b-3c)

c)
12x+36y = 12(x+3y)
y-3y = y(1-3) ewentualnie = -2*y
15a²+12b = 3(5a²+4b)

d)
24x²-16y = 8(3x²-2y)
12a²-8b = 4(3a²-2b)
10n-15m = 5(2n-3m)
7 3 7